Comparative Study of Acute Stress in Infants Undergoing Percutaneous Achilles Tenotomy for Clubfoot vs. Peripheral Line Placement - Anna Ey Batlle; Iolanda Jordan; Paula Miguez Gonzalez; Marta Vinyals Rodriguez (MDPI AG, 2024)
Introduction: Percutaneous tenotomy of the Achilles tendon is a procedure that is part of the Ponseti method for clubfoot correction. The need to apply general anesthesia or sedation for this procedure is controversial. The objective of this study is to compare the acute stress generated in infants by percutaneous Achilles tenotomy under local anesthesia vs. peripheral line placement. Material and methods: This cross-sectional study compares the discomfort experienced by 85 infants undergoing percutaneous Achilles tenotomy with local anesthesia with that experienced by 39 infants undergoing peripheral line placement. The following parameters were determined: the duration of the procedure, crying time, average crying intensity, and maximum crying intensity. Other data recorded included the infant's age and complications arising during the procedure. Results: The mean ages of these patients were 1.95 and 2.18 months, respectively. The following data were obtained: the mean duration of the procedure for Group A was 8.13 s and for Group B it was 127.43 s; the mean duration of crying for Group A was 84.24 s and for Group B it was 195.82 s; the mean intensity of crying for Group A was 88.99 dB and for Group B it was 100.98 dB; and the maximum crying intensity for Group A was 96.56 dB and for Group B it was 107.76 dB. Conclusions: Percutaneous Achilles tenotomy can be safely performed as an outpatient procedure, under local anesthesia. This method generates less discomfort than peripheral line placement.